2020
DOI: 10.1002/agj2.20027
|View full text |Cite
|
Sign up to set email alerts
|

Response of potato to nitrogen and phosphorus fertilizers at Assosa, western Ethiopia

Abstract: Low soil fertility is one of the critical factors limiting the productivity of potatoes (Solanum tuberosum L.) in western Ethiopia. The field experiment was conducted in the 2015 and 2016 cropping seasons to elucidate the response of potato yield, yield components, tuber quality to nitrogen and phosphorus fertilizer, and their economic benefit. The treatment comprised five levels of nitrogen (0, 50, 100, 150, and 200 kg N ha −1 ) and five levels of phosphorus (0, 50, 100, 150, and 200 kg P 2 O 5 ha −1 ). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
7
5
0
Order By: Relevance
“…The highest plant height, 76.82 cm, was recorded under N3. This increase of plant height with N dosage was also reported in previous research (Godebo and Belay 2020;Setu and Mitiku 2020;Tolessa et al 2017). Sebnie et al (2021) indicated that an application of mineral N fertiliser increased potato plant height compared to unfertilised plots.…”
Section: Plant Growthsupporting
confidence: 87%
“…The highest plant height, 76.82 cm, was recorded under N3. This increase of plant height with N dosage was also reported in previous research (Godebo and Belay 2020;Setu and Mitiku 2020;Tolessa et al 2017). Sebnie et al (2021) indicated that an application of mineral N fertiliser increased potato plant height compared to unfertilised plots.…”
Section: Plant Growthsupporting
confidence: 87%
“…The same comparison across the N fertilization treatments showed an increase in plant height with an increase in nitrogen rate. The same result was found by previous research (Tolessa et al, 2017;Godebo and Belay, 2020;Setu and Mitiku, 2020). The number of branches/plant and HI significantly increased with an increase in nitrogen rate (table 7).…”
Section: Yield Componentssupporting
confidence: 91%
“…These results are not in agreement with the findings of Fandika et al (2016) andEl Mokh et al (2015), who reported that potato tuber number per plant increased with irrigation amount. These findings aligned with those of Ayyub et al (2019) and Setu and Mitiku (2020), who also found that an increment in the amount of N statistically increased tuber number plant. Moreover, El Mokh et al (2015) indicated that a low tuber number per plant decreased the total potato tuber yield.…”
Section: Yields Components Of Apical Rooted Cuttings Of Potato Grown In Mollic Andosols Under Different N and Irrigation Regimessupporting
confidence: 88%
“…The maximum marketable tuber yield of 54.25 t ha À1 achieved in Mollic Andosols of this study can be attributed to the significant interaction effect observed between the two factors. This finding confirmed the results of Zewide et al (2012), Getie et al (2015), El Mokh et al (2015, Regassa et al (2016), Ayyub et al (2019), Setu and Mitiku (2020) and (Tang et al, 2021), who reported that marketable potato yield significantly increases with N dosage. This study suggests further research using higher N rates above the rates used to find the N level from which an increase in the amount of N in Mollic Andosols might decrease potato yield.…”
Section: Yields Components Of Apical Rooted Cuttings Of Potato Grown In Mollic Andosols Under Different N and Irrigation Regimessupporting
confidence: 88%